The correlation between SERVQUAL dimensions and student satisfaction / Nur Zihan Abd Rashid, Tuan Nur Athirah Nabilah Tuan Ismail and Bibianah Thomas - Abd Rashid, Nur Zihan; Tuan Ismail, Tuan Nur Athirah Nabilah; Thomas, Bibianah (Universiti Teknologi MARA, 2021)
Service quality is a crucial element in ensuring the competitiveness of many types of institutions. Having good service quality enhances the reputation of an organization and thus becomes their added competitive advantage. In higher education institutions, service quality is important in ensuring students, as the primary stakeholders, have a good learning experience. This subsequently influences student satisfaction levels. The primary objective of this paper is to analyze the correlation between five elements in SERVQUAL dimensions (tangibility, reliability, responsiveness, assurance, and empathy) and students' satisfaction. Questionnaires were distributed among students attending various faculties at UiTM Sabah using the convenience sampling technique. In total, 250 questionnaires were collected for analysis. Overall, the results show that the students are satisfied with the service quality at UiTM Sabah. Specifically, all five SERVQUAL dimensions correlated with student satisfaction. The reliability, responsiveness, assurance, and empathy dimensions demonstrated a strong correlation with student satisfaction. Meanwhile, tangibility had a moderate correlation with student satisfaction. This study aims to contribute knowledge to the service quality field, especially in higher education institutions. In the final section of this study, it is proposed that future research investigate different perspectives of service quality.